Is the threshold for postoperative prosthesis-patient mismatch the same for all prostheses? - Okamura, Homare; Yamaguchi, Atsushi; Morita, Hideki; Naito, Kazuhiro; Yuri, Koichi; Adachi, Hideo (Surgery today (Tokyo, Japan), 2013)
Purpose The effective orifice area index (EOAI) is used to define the prosthesis-patient mismatch (PPM) after aortic valve replacement (AVR). However, few studies have so far evaluated whether the cutoff value for PPM varies across prostheses. This study assessed the hemodynamics in patients given a mechanical valve and then re-evaluated the validity of the commonly accepted threshold. Methods The subjects included 329 patients that underwent AVR with a St. Jude Medical Regent valve. The transvalvular pressure gradient and EOAI were determined echocardiographically, and the commonly accepted threshold was analyzed in relation to survival. Results The mechanical valves very often yielded a postoperative transvalvular pressure gradient >10 mmHg, and thus, clinically significant residual pressure, regardless of the EOAI. The slope of the curve describing the relationship between the transvalvular pressure gradient and EOAI was gentler than that reported for bioprosthetic valves, for which the pressure gradient rises sharply at EOAI <0.85 cm 2 /m 2 . The commonly defined PPM did not affect the long-term survival or regression of the left ventricular mass index. Conclusions The relationship between the transvalvular pressure gradient and the EOAI in patients given a mechanical prosthesis differed from the reference standard. These data suggest the need to reconsider the appropriate cutoff value for PPM in relation to different prostheses.